A facile one-step sustainable synthesis of magnetic hyperbranched dendritic polyester HBPE for efficient trace removal of lead and copper ions - Salma Habib (10971426) (2024)
In this article, a single-step procedure to conjugate iron oxide magnetic nanoparticles (MNPs) to Boltorn polymer is developed resulting in a tailored and engineered nanocomposite used for the first time for heavy metal trace removal targeting the lead and copper ions. Boltorn H40 was successfully loaded on the surface of Fe3O4 during magnetic modification, resulting in magnetic Boltorn that can be easily removed from water after the adsorption process. Bol@MNPs could remove Pb2+ and Cu2+ from water in different mechanistic forms. Factors that directly affect the adsorption performance including adsorbent dosage, contact time, pH, and initial concentration were studied. The adsorptive behavior of the new nanocomposite Bol@MNPs for lead and copper aligns with the Langmuir and pseudo-second order kinetic models. The average removal rates for Pb2+ and Cu2+ were 96 % and 80 %, with maximum capacities of 1.546, and 2.043 mg/g respectively, and the mechanism of adsorption includes complexation, electrostatic interactions, and chelation explained by the abundance of hydroxyl groups in the nanocomposite. The adsorption effect of ions in the binary system revealed a synergetic behavior for lead ions. Overall, the synthesized nanocomposite shows excellent stability for sustainable reuse. These results support a promising advancement in developing sustainable materials with enhanced Cu and Pb trace metal ion removal efficiency. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2024.105280